Estilos de vida de los clientes y calidad de servicio de la asociación de comerciantes agro artesanal San Borja - Polo Cerna, Dora Alejandrina (2019)
This research entitled: Lifestyle and quality customer service the business assocation artisanal agro San Borja (ACMSB), generally aimed at determining the relationship between the lifestyles of our customers and quality service employers in the ACMSB, the specific objectives were: To identify the lifestyles of our customers, know the customer perception about the quality of service for entrepreneurs ACMSB. The general method used was the scientific method, the instruments were two questionnaires Servqual and lifestyles. The sample consists of 171 clients, men and women over 18, whose consumption exceeded the S/.10.00 and the day of the survey were buying goods and services ACMSB facilities are included domestic workers and excluded clients over 80 years. The hypothesis was: There is a relationship between lifestyle and quality of service for customers ACMSB. For data analysis was done using descriptive statistics and hypothesis testing for inferential analysis. Pearson test sheds 0,746 which mean there is a ratio of 74% between service quality and lifestyles of customers in the traditional agro business association of San Borja. The lifestyle of the customers is the modern ACMSB, this result agrees with the findings of Arellano [1] who reported that the modern lifestyle is preponderant in our country. The finding found by De Soto [2] that the newcomers from the countryside to the city, found an impenetrable wall of rules, that marginalized social and economic activities legally established, in which it was extremely difficult to get into formal business was has been overcome, since these micro and small businesses are viable, legal, and are still very well regarded by customers. Major argument is the statistical report INEI [3], which reports that business grew by 10.96%, this is a positive trend in most of its component items, highlighting among others, retail food through supermarkets and hypermarkets and department stores. It concludes that companies in the retail sector especially the ACMSB are reinventing strategies around customer satisfaction and are aware of the encroachment of large chains of supermarkets and hypermarkets and department stores. This research will serve as a basis for future strategies to be adopted by employers in the ACMSB, in order to keep customers satisfied with high quality service.